ANALYSIS PETRUCHIO'S STRATEGIES IN STRUGGLING HIS LOVE - MAS DARUL IHSAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
In the play, Kate, the main female character, is described as a young wealthy and beautiful woman, but she is not considered as a virtuous woman because of her shrewishness, Therefore, the researcher eager to learn and discuss the significance of the idea of an ideal wife in this play since it may show what kind of behavior that has been associated with virtue in a woman to be an ideal wife. It may reveal how a wife should behave that she deserves to be considered as an ideal wife. Then while analyzing Shakespeare's the taming of the shrew the researcher find out that Petruchio’s treatment of his wife who is considered as a shrew implies a process of education that is aimed at teaching Kate to be a real woman. Thus, the order is achieved. The perpose of this research is the researcher going to discuss Petruchio's reasons in marrying Kate and to discuss the way Pertruchio changes Kate.